Hipoparatireoidismo primário em cão - Freitas, Mateus do Amaral [UNESP]; Jark, Paulo Cesar [UNESP]; Palumbo, Mariana Isa Poci [UNESP]; Lourenco, Maria Lucia Gomes [UNESP]; Machado, Luiz Henrique de Araujo [UNESP] (Univ Estadual Londrina, 2014)
The hypoparathyroidism is a rare endocrinopathy reported in dogs, caused by a deficiency in the synthesis of parathyroid hormone (PTH). The lack of PTH causes hypocalcemia and hyperphosphatemia, resulting in a series of neurological and neuromuscular disorders. Unlike most endocrinopathies, hypoparathyroidism is a disease in which the exogenous hormone replacement is not being viable, becoming the treatment a challenge. The present report aims to describe a case of primary hypoparathyroidism in a Schnauzer dog with seizures and neuromuscular disorders, and successful treatment employed, this being the first case, according to the literature, of hypoparathyroidism diagnosed in Brazil. The hypoparathyroidism should be considered as a differential diagnosis in cases of seizure. A complete neurological evaluation and determination of serum ionized calcium and parathyroid hormone are essential for the diagnosis of this disease. Early diagnosis may improve the quality of life of affected animals, since after the initiation of therapy, there is complete remission of clinical signs.
Primary hypoparathyroidism in a dog
Keywords: Deficiency; hypocalcemia; parathyroid hormone; dog